The evaluation of software requirement specifications for software testers / Rifhan A Rahim - A Rahim, Rifhan (2017)
Software engineering plays big part in the software development. Software engineering is the establishment and use of sound engineering principles in order to obtain economically software that is reliable and works efficiently on real machines. One of the branch of software engineering is requirement engineering, which deals with requirements elicitation, refinement, and analysis of software system requirements. However, requirement engineering is not an easy task. Software's requirement has always been an issue in requirement engineering world. It has been long recognized that inadequate, incomplete, ambiguous, or inconsistent requirements have a significant impact on the quality of software. The research background for this paper is how the software requirement specification can be an important factor to the overall software quality. When the software requirement is complete, understandable, and not vague, the development of the software is much easier. With the improved of quality of requirement specifications that would be provided to the developer, which in turn will also directly relate to the quality of the software product. The research aim and objective is to identify the common issues or barriers in software requirement specification, and to develop a checklist or template which will map the issue and the requirement. The checklists template will be useful to be as the reference for business analysts, system analysts, external users and other stakeholders. The research method for this project is qualitative methods to achieve the study findings. The qualitative methods that have been chosen is interview with the practitioners and experts with related field. This project utilized mainly qualitative data collection in collecting the views from experts and practitioners. For the finding, researcher able to summarise list of the common issues or barriers in software requirement specification and develop a checklist or template which will map the issue and the requirement.